Dynamic measurement of carbon fiber bundles and single fibers - Zhang, Kaiwen (2014)
The measurement of the mechanical behaviours of carbon-fiber bundles and three types of single fibers, namely carbon fibers, pure CNT fibers and composite CNT fibers, at both quasi-static and high strain rates is featured in this study. To determine the tensile behaviours at high strain rates, two novel types of free-falling Hopkinson tension bars were designed. Finite element analysis was done using Simulia Abaqus to study the dynamic failure mechanisms of single fibers.